Good Stress Management Capability Is Associated with Lower Body Mass Index and Restful Sleep in the Elderly - Teraoka, Seitaro; Hayashida, Naomi; Shinkawa, Tetsuko; Taira, Yasuyuki; Nagai-Sekitani, Yui; Irie, Sumiko; Kamasaki, Toshihiko; Nakashima-Hashiguchi, Kanami; Yoshida, Koji; Orita, Makiko; Morishita, Michiko; Clancey, Gregory; et al. (The Tohoku Journal of Experimental Medicine, 2013)
Psychosocial stress is generally associated with adverse health behaviors and has been linked to the development of cardiovascular diseases (CVD). Recently, an individual's sense of coherence (SOC), which is a concept that reflects the ability to cope with psychosocial stress, has been recognized as an essential component of long-term health and stress management. The association between SOC and traditional and alternative atherosclerotic markers in a community sample, however, has not been thoroughly investigated. In the present study, we evaluated stress management capability and psychological conditions using the Japanese version of the Sense of Coherence-13 (SOC-13) Scale, supplemented by the General Health Questionnaire-12 (GHQ-12) that screens for minor psychiatric disorders. The study subjects were 511 adults, median age 64 years (range 48-70), who participated in a regular medical screening program in Nagasaki Prefecture, Japan. We then correlated our findings with atherosclerotic risk factors in the same community sample, such as body mass index (BMI) and proper and regular sleeping habits. We found that close association between good stress management capability and lower BMI and/or regular sleeping habits in elderly Japanese. This provides strong evidence that BMI and sleep management are contributory to SOC. If the ability to cope with psychosocial stress is important to the prevention of CVD, then weight control and proper sleep habits must be emphasized from a psychosocial stress-management perspective as well as a physical one.